Peran Lembaga Pondok Pesantren Dalam Pendidikan Karakter Di Pondok Pesantren Al-Rahmah - Muhammad Iskandar; Nadya Delima Fitria (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to determine character education in Islamic boarding schools and the prevalence of issues of violence in Islamic boarding schools, so the researcher wants to discuss in more depth about character education and issues of violence that are currently widespread in Islamic boarding schools with the object of research being the Al-Rahmah Islamic boarding school. . The approach method used is a qualitative method with data collection techniques of observation, interviews and documentation. The data collected by researchers is more focused on several research objectives, namely: 1) describing modern Islamic boarding schools based on the times. 2) describe Islamic boarding school institutions in character education 3) analyze more deeply the issues of violence in Islamic boarding schools, Islamic boarding schools are places where education about the Islamic religion focuses on Islamic religious studies and does not eliminate contemporary elements in the current era. more modern, especially in modern-based Islamic boarding schools.